2016
DOI: 10.1002/hbm.23449
|View full text |Cite
|
Sign up to set email alerts
|

On the brain structure heterogeneity of autism: Parsing out acquisition site effects with significance‐weighted principal component analysis

Abstract: Neuroimaging studies have reported structural and physiological differences that could help understand the causes and development of Autism Spectrum Disorder (ASD). Many of them rely on multisite designs, with the recruitment of larger samples increasing statistical power. However, recent large‐scale studies have put some findings into question, considering the results to be strongly dependent on the database used, and demonstrating the substantial heterogeneity within this clinically defined category. One maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
(86 reference statements)
0
29
0
1
Order By: Relevance
“…This has been made possible with the availability of 3 T structural MRI data from existing databases, which are summarised in Table 2. An alternative is to aggregate MRI data from multiple sites, however this would necessitate including the site as a variable in the analysis, as the effect of this covariate may be significant (Auzias et al, 2016; Martinez‐Murcia et al, 2017). Another important consideration is accounting for confounding variables, in order to elucidate the true impact of brain structure on symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This has been made possible with the availability of 3 T structural MRI data from existing databases, which are summarised in Table 2. An alternative is to aggregate MRI data from multiple sites, however this would necessitate including the site as a variable in the analysis, as the effect of this covariate may be significant (Auzias et al, 2016; Martinez‐Murcia et al, 2017). Another important consideration is accounting for confounding variables, in order to elucidate the true impact of brain structure on symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested applying a significance-weighted principal component analysis (PCA) technique to reduce the undesired intensity variance, thereby increasing the statistical power in detecting the differences between ASD and DC groups [60]. Using this technique, Broca's area and temporal-parietal junction were found to be significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…There is a hypothesised role of fT in atypical neurodevelopment through associative studies from our group which show significant association of elevated fT levels with autism when compared to typical individuals, and fT levels were positively associated with higher scores on the Childhood Autism Spectrum Test (CAST) and the Child Autism Spectrum Quotient (AQ‐Child) . The brain region RTPJ, which has been shown to have a greater volume with increased fT, is also known to be associated with autism . Additionally, elevated testosterone levels have been positively associated with occurrence of obsessive compulsive disorder, and Tourette syndrome, whereas elevated levels of gestational oestrogens have been suggested to increase predisposition to schizophrenia …”
Section: Steroid Hormones In the Typical And Atypical Brainmentioning
confidence: 78%